Brain M-App’s Structure and Usability: A New Application for Cognitive Rehabilitation at Home - Pedroli, Elisa; Mancuso, Valentina; Stramba-Badiale, Chiara; Cipresso, Pietro; Tuena, Cosimo; Greci, Luca; Goulene, Karine; Stramba-Badiale, Marco; Riva, Giuseppe; Gaggioli, Andrea (Frontiers in Human Neuroscience, 2022)
Cognitive frailty is defined as a clinical condition characterized by both physical frailty and cognitive impairment, without reaching the criteria for dementia. The major goal of rehabilitation intervention is to assist patients in performing ordinary personal duties without the assistance of another person, or at the very least to remove the need for additional support, using adaptive approaches and facilities. In this regard, home-based rehabilitation allows patients to continue an intervention begun in a hospital setting while also ensuring support and assistance when access to healthcare systems is limited, such as during the present pandemic situation. We thus present Brain m-App, a tablet-based application designed for home-based cognitive rehabilitation of frail subjects, addressing spatial memory, attention, and executive functions. This app exploits the potential of 360° videos which are well-suited to home-based rehabilitation. The Brain m-app is made up of ten days of activities that include a variety of exercises. The activities were chosen based on those patients used to do during their clinical practice in the hospital with the aim to improve their independence and autonomy in daily tasks. The preliminary usability test, which was conducted on five older people, revealed a sufficient level of usability, however, the sample size was modest. Results from the clinical study with 10 patients, revealed that Brain m-App improved especially executive functions and memory performances.